2013
DOI: 10.1136/bcr-2012-008463
|View full text |Cite
|
Sign up to set email alerts
|

Omental flap for treatment of long standing lymphoedema of the lower limb: can it end the suffering? Report of four cases with review of literatures

Abstract: We report our experience of four cases of long-standing unilateral, secondary lymphoedema of the lower limb, for which conservative treatment has failed, that were treated in our centre using pedicled omental flap. The four patients were followed for a period of 1 year after the procedures and frequent measurements of the circumference of the affected limb revealed a reduction in the circumference ranging between 50% in the first patient to 75% in the fourth patient together with an excellent functional improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…This approach resulted in an iatrogenic hernia, which led to some severe complications, and limited widespread adoption of this technique . The advent of microsurgery has reignited interest in the omentum flap, as this approach would allow transplantation to virtually anywhere in the body, and the abdomen to be closed completely . Although laparoscopic harvest of the omentum has also been described, in our experience open harvest through a limited incision is more precise and remains the preferred approach.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This approach resulted in an iatrogenic hernia, which led to some severe complications, and limited widespread adoption of this technique . The advent of microsurgery has reignited interest in the omentum flap, as this approach would allow transplantation to virtually anywhere in the body, and the abdomen to be closed completely . Although laparoscopic harvest of the omentum has also been described, in our experience open harvest through a limited incision is more precise and remains the preferred approach.…”
Section: Discussionmentioning
confidence: 96%
“…Vascularized omentum lymphatic transplant (VOLT) is a promising technique in the surgical treatment of lymphedema . The omentum contains an abundant supply of lymphatic tissue over a large surface area, making it a viable option for lymphatic reconstruction, especially for patients who have limited peripheral donor site options because of prior surgery, and radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Saad et al selected 4 patients with persistent lower limb lymphedema and invalid conservative treatment to perform omentoplasty. 13 The lymphedema of the 4 patients were improved significantly after operation.…”
Section: Omentoplastymentioning
confidence: 81%
“…19,56 Previous studies using the GOLF reported an improvement in circumferential difference from 2% to 29%, 57 circumferential reduction rate between 9% and 22.2% for upper extremity lymphedema, 58 and from 50% to 75% for lower extremity lymphedema. 59 Recently, Nguyen et al reported the long-term outcome of 42 patients who underwent GOLF with a mean improvement in volumetric difference of 22% and good subjective improvements. 61 However, limited long-term data are available regarding the sequelae following GOLF harvest, particularly on digestion and intraperitoneal immune maintenance.…”
Section: Greater Omental Lymph Node Flap (Golf)mentioning
confidence: 99%